2020
DOI: 10.1111/ijfs.14679
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the use of lactic acid bacteria and Thymus vulgaris essential oil on Suffolk and Ile de France lamb breed (MuscuIus gluteus) quality parameters

Abstract: In the present study, Lactobacillus plantarum (LUHS135), Thymus vulgaris essential oil (0.1% v/v) and their combination were used to treat Suffolk and Ile de France lamb meat. Changes in the microbiological profile and physicochemical parameters of meat were evaluated after 24 h of treatment at 4°C. Treatments resulted in significantly lower mould/yeast, total enterobacteria (by up to 45%) counts, water-holding capacity (by 21-63%) and cooking loss (by 17-35%) in all samples. Moisture content increased, on ave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 63 publications
1
19
0
Order By: Relevance
“…For this reason, new strategies are sought to improve the lamb meat technological process to obtain safer products. It has been reported that a Lactobacillus plantarum strain isolated from bread sourdough, Thymus vulgaris essential oil (at a concentration of 0.1% v/v), and their combination can be used for the pre-treatment of lamb meat [73]. The pre-treatments reduced mould and yeast, as well as total enterobacteria numbers, in lamb meat samples.…”
Section: Sourdough Lab-plant-based Bioproducts For Increasing the Fun...mentioning
confidence: 99%
“…For this reason, new strategies are sought to improve the lamb meat technological process to obtain safer products. It has been reported that a Lactobacillus plantarum strain isolated from bread sourdough, Thymus vulgaris essential oil (at a concentration of 0.1% v/v), and their combination can be used for the pre-treatment of lamb meat [73]. The pre-treatments reduced mould and yeast, as well as total enterobacteria numbers, in lamb meat samples.…”
Section: Sourdough Lab-plant-based Bioproducts For Increasing the Fun...mentioning
confidence: 99%
“…These EOs were investigated by Govaris et al (2010), Karabagias et al (2011), Kumar et al (2018), and Klupsaite et al (2020) in sheep meat, with good reductions in the microbial load at relatively low concentrations (0.1%-0.9%). Positive results were also obtained with Syzygium aromaticum EO (Aliakbarlu & Khalili Sadaghiani, 2015;Kumar et al, 2018;Vrinda Menon & Garg, 2001), mainly because of its eugenol content, which can destroy the membrane and cause leakage of cellular material (Bennis et al, 2004) but also with other EOs, like Zataria multiflora, Cuminum cyminum, Allium sativum, and Cinnamomum cassia (Aliakbarlu & Khalili Sadaghiani, 2015;Emam et al, 2021;Z.…”
Section: Application Of Essential Oils On Sheep Meatmentioning
confidence: 99%
“…Antimicrobial activity was enhanced when two or more biopreservatives were used in combination with each other or with another antimicrobial substance but also when EOs were used in combination with other hurdles, like MAP or VP (Govaris et al, 2010;Z. Hussain et al, 2021;Karabagias et al, 2011;Klupsaite et al, 2020;Kumar et al, 2018;Lahmar et al, 2018;Nemati et al, 2019). For example, Govaris et al (2010) showed how the combination of O. vulgare EO and nisin gave better results than when the two substances were used individually because the disintegration of the cell membrane by the EO could also have led to a greater sensitivity to nisin (Moosavy et al, 2008).…”
Section: Application Of Essential Oils On Sheep Meatmentioning
confidence: 99%
See 1 more Smart Citation
“…Different technologies have been applied to improve LM quality parameters, e.g., sonication [ 15 , 16 ] and thermal processing [ 7 , 17 , 18 ]. Additionally, the pre-treatment of LM with natural marinades has also been reported [ 19 , 20 , 21 ]. This solution is of great interest because, currently, consumers are looking for natural, high-quality, and acceptable products.…”
Section: Introductionmentioning
confidence: 99%